Intimate Partner Violence Against Transgender Women: Prevalence and Correlates in Lima, Peru (2016–2018) - Murphy, Ellen C. (2020)
Limited data exists on intimate partner violence (IPV) among transgender women (TW), though global trends suggest IPV is associated with HIV risk in this population. We describe the prevalence of verbal, physical, and/or sexual violence as well as participant- and partner-level correlates of IPV among TW in Lima, Peru. Among 389 respondents, 15.2% reported IPV with one or more of their last three sexual partners: 9.2% verbal, 8.2% physical, and 2.3% sexual violence. Physical and verbal violence were more common with stable partners (aPR 3.46, 95% CI 1.17–10.25, aPR 2.46, 95% CI 1.14–5.28, respectively). Physical violence was associated with condomless receptive anal intercourse (cRAI) (aPR 2.22, 95% CI 1.19–4.13) and partner alcohol use (aPR 4.38, 95% CI 1.56–12.33) while verbal violence correlated with participant inebriation (aPR 4.86, 95% CI 1.63–14.46). Our results link IPV with stable partnerships, alcohol use, and cRAI, suggesting TW in Peru may benefit from multidimensional IPV prevention strategies to foster supportive relationships and reduce HIV transmission.